From Clicks to Cradles: Mapping the Digital Landscape of Maternal Support through Bibliometric Analysis - Rita Wong Mee Mee; Hanim Mohamad Ismail; Belinda Marie Balraj; Lim Seong Pek; Ali Derahvasht; Yang Mingmei (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Online platforms have emerged as crucial parenting information sources in the digital age, revolutionizing how moms seek help, make choices, and deal with the difficulties of raising children. This change demonstrates the increasing scholarly interest in comprehending how digital resources affect the experiences of mothers. With an emphasis on performance and co-citation analyses, this study offers a bibliometric analysis of studies on mothers' interactions with online parenting resources. After a thorough screening process, 453 studies were eventually included out of the 1,352 records that were first found using the Web of Science database. While co-citation analysis finds thematic clusters like maternal mental health, digital parenting literacy, and online community engagement, performance analysis identifies important contributors, such as top authors, organizations, and nations. The findings show that, especially in reaction to the COVID-19 pandemic, academics are increasingly focusing on digital platforms as the main sources of parenting information. The results indicate that although mothers can benefit greatly from online resources, problems with disinformation and inequalities in digital literacy still exist. Since it highlights the necessity of trustworthy digital parenting resources to support maternal mental health and child development, this study is in line with Sustainable Development Goal (SDG) 3: Good Health and Well-Being. For a more comprehensive understanding of digital parenting practices, future research should incorporate qualitative methods and investigate cross-cultural viewpoints. A systematic road map for upcoming studies, the creation of policies, and real-world applications in the rapidly changing field of online parenting support is offered by this bibliometric analysis.